Holoprosencephaly: The Disease and Its Related Disabilities - Balconara, Desireè; La Cognata, Daria; Zanghì, Antonio; Vecchio, Michele; Marino, Francesco; Sortino, Giuseppe; Belfiore, Giuseppe; Basile, Antonio; Falsaperla, Raffaele; Praticò, Andrea D. (Journal of Pediatric Neurology, 2024)
Holoprosencephaly (HPE), the most prevalent developmental anomaly affecting the forebrain in humans, occurs in approximately 1 in 16,000 liveborn neonates, with an incidence reaching 1 in 250 in conceptuses. This condition is distributed worldwide. HPE is etiologically heterogeneous, and its pathogenesis is variable. Environmental, teratogenic, genetic, or metabolic factors can contribute to the development of HPE. Notably, maternal insulin-dependent diabetes mellitus and maternal alcoholism are among the primary causative factors. HPE may be linked to various well-defined multiple malformation syndromes characterized by a normal karyotype, such as Smith–Lemli–Opitz's, Pallister–Hall's, or velocardiofacial syndrome. Alternatively, it can be associated with chromosomal abnormalities. (i.e., Patau's syndrome and, less frequently, Edwards' syndrome or Down's syndrome). The major genes implicated in HPE are SHH, ZIC2, SIX3, and TGIF. The range of HPE is extensive, covering diverse neuropathological phenotypes of varying severity. Three classical types of HPE can be distinguished in increasing order of severity: lobar HPE, characterized by separated right and left ventricles with some continuity across the frontal cortex; semilobar HPE, featuring a partial separation; and the most severe form, alobar HPE, where there is a single brain ventricle and the absence of an interhemispheric fissure. Additionally, there are other variations of HPE, ranging in severity, including the less severe interhemispheric median HPE (also known as middle interhemispheric variant). The phenotypic spectrum of HPE is highly extensive, encompassing severe cerebral malformations to microforms. Children with HPE often encounter numerous medical challenges; among them neurological disorders, craniofacial malformations, endocrine disorders, oral and motor dysfunction, and dysfunction of the autonomic nervous system. Neurologic problems, such as cerebral palsy and seizures, are common. The diagnosis of HPE is typically made prenatally, relying primarily on ultrasound and magnetic resonance imaging examinations. The prognosis for individuals with HPE is largely dependent on its underlying causes. Those with cytogenetic abnormalities, in particular, face a significantly poorer prognosis, with only 2% surviving beyond 1 year.
Keywords: holoprosencephaly; genetic; brain malformations; intellectual; disability